An Evaluation Of Tioman Island Marine Park Zoning Process - Sulaiman, Mohd Bashir (2013)
Malaysia has become a tourist destination for domestic and foreign tourists. The Malaysian government has gazetted its Marine Parks in 1994 under the Fisheries Act (1985), to protect and to ensure a sustainable management of Marine Parks. However, due to the weaknesses in the zoning process and in the management system, some famous Marine Parks around Malaysia have been closed. Zoning of Marine Park is a method to protect the biological biodiversity and to ensure the sustainability of marine lives. This study looks at the current policy and practice of Marine Park zoning process in Pulau Tioman and proposes a proper marine park zoning process to achieve a sustainable Marine Park management system in Pulau Tioman. Specifically, this study will look at the Marine Park zoning process, which includes the zoning stages, the types of zoning, and the zoning function. This study adopts a multimethods approach comprising three methods of using secondary data from the report prepared for Pulau Tioman, conducting interviews with the respondents involved in the management and zoning of Tioman Island, and making site observations, to collect data regarding the implementation and management of Tioman Island Marine Park. The results proved that zoning plan prepared in the secondary reports were ineffective in controlling the activities on the Pulau Tioman. Meanwhile, the site observation on Tioman Island showed that the activity control on the Marine Park was weakly implemented. Results from the interviews also supported the findings, and the respondents agreed that improved zoning process will create a sustainable Marine Park.